A Three-dimensional Perspective on Wrongful Convictions in Israel: Organizational-Forensic, Psychosocial and Practical - Peled-Laskov, Ronit; Shoham, Efrat (International Journal of Criminology and Sociology, 2015)
It is difficult to find an injustice committed against the citizen by the state that is greater than the conviction of an innocent person. At this stage, it may be tentatively stated that the phenomenon is not insignificant. This theoretical article describes the various aspects of the criminal justice system associated with the undesirable outcome of wrongful convictions. The paper reviews a series of organizational and forensic aspects that could bring about a bias in investigation of the legal truth. Furthermore, a number of psychosocial aspects relating to wrongful convictions, followed by practical aspects are described and discussed. It appears that on the practical level the phenomenon cries out for changes in the law enforcement system (e.g. implementation of the US Innocence Project or the biometric databank) and the need for empirical investigation. It appears that there is still a long way to go before a full understanding can be obtained of wrongful convictions and their prevention. One way or another, the authors are of the opinion that greater academic and public importance should be assigned to the question of wrongful convictions and perhaps turn the issue of truth and falsehood in criminal law into a theoretical and research field in its own right.